Kegiatan Pengabdian Kepada Masyarakat (PKM) Berbasis Pengajaran Bahasa Inggris Interaktif - Nayla Zahra Basyalwi; Dwi Astuti Wulandari; Qiara Kaila Ayynda; Shella Mitha Adelia; Kamil Ghiffary Abdurrahman (Lembaga Pengembangan Kinerja Dosen, 2025)
Educational inequality in Indonesia remains a significant challenge, as reflected in the low proportion of citizens with higher education degrees and the predominance of high school graduates as the highest educational attainment. University students, as part of the educated minority, hold a moral responsibility to redistribute the academic privilege they possess to the broader community. This article presents a report on a Community Service Program (PKM) titled It’s English Buddy, an online English-teaching initiative launched by students of the International Relations Study Program at UPN Veteran Jakarta. The program offers individual and group English conversation sessions at affordable prices, adopting a non-distributing profit approach to ensure operational sustainability. Supported by literature on the effectiveness of online learning in enhancing academic performance through flexibility and accessibility, the program has successfully reached participants of various ages and backgrounds. The results show that most participants are women and were recruited primarily through personal networks, highlighting the importance of public communication strategies and trust-building. Overall, It’s English Buddy demonstrates the potential of student-led grassroots educational initiatives as a meaningful contribution to expanding learning opportunities within society.